Experimental and Numerical Simulation of Dry Pressure Drop in High‐Capacity Structured Packings. Issue 6 (18th March 2016) - Amini, Younes; Karimi‐Sabet, Javad; Esfahany, Mohsen Nasr
Abstract: Experimental and numerical studies were conducted on the performance and capacity of structured packings for mixture separation with very low separation factor. Different formations and conditions of the innovative structured packing PACK‐2100 with high surface area were studied to evaluate the main characteristics such as dry pressure drop. In addition, numerical simulation was performed to describe the details of the flow structure in these modified structured packings. Three‐dimensional computational fluid dynamics modeling of PACK‐2100 allowed for comparing the pressure drop in both laminar and turbulent flow regime. The obtained experimental and numerical data demonstrate the potential contribution of the packing to high‐efficiency systems with low separation factor. Abstract : The performance of a structured packing is strongly related to the variation of the pressure along the flow stream. Experiments and computational analyses were performed to investigate the potential benefits of an innovative wire gauze structured packing. Various conditions and evaluations such as packing angles and comparison of commercial packings were studied.